Crisis and Organisational Innovation: Icelandic Local Government Responses - Anna Cregård; Rolf Solli; Patrik Zapata (Central European Public Administration Review)
This article examines the relationship between radical change in an institutional context and organisational innovation. It is based on an exploratory case study of three Icelandic local governments conducted in autumn 2010 and summer 2011. While many crises, when scrutinised closely, appear to be more like threats of crisis, Iceland’s economic crisis is a genuine crisis with real and immediate effects. The three local governments studied responded to the crisis with actions that promote cooperation, reorganisation, acquiescence and involvement. The study demonstrates that most of these actions were reactive and somewhat non-innovative, though some were innovative – at least in this particular context.